Can gender quotas prevent risky choice shifts? The effect of gender composition on group decisions under risk - Katharina Lima de Miranda; Lena Detlefsen; Ulrich Schmidt (Kiel Institute for the World Economy (IfW), 2019)
This study contributes to the public debate on gender quotas and the literature on gender and risk taking by analysing how the level of risk taking within a group is influenced by its gender composition. In particular we look at the shift of risk taking between group and individual decisions and analyse to which extent this shift depends on the gender composition. We derive a gender-specific polarization hypothesis which states that compared to individual preferences, male dominated groups will shift towards higher risk taking than female dominated ones. Our experimental tests reveal a systematic impact of gender composition on group shifts which supports our hypothesis and points into the direction that a higher share of females may prevent excessive risk taking.
Keywords: 330; risky shift; risk taking; group decisions; gender; monetary incentives